Examining the role of transformational leadership and entrepreneurial orientation on employee retention with moderating role of competitive advantage - Mohammad Ali Yousef Yamin (Management Science Letters, 2020)
This study aims to investigate employee motivational and environmental factors and their effects on employee retention and organizational performance. Employee retention is predicted by organizational environment, intrinsic motivation, organizational learning, knowledge management, entrepreneurial orientation, external connect and explained R2=76.3% of the variance in employee retention. Therefore, organizational performance is predicted by competitive advantage and employee retention and explained R2=19.9% of the variance in organ-izational performance. Effect size analysis indicates that intrinsic motivation had substantial effect on size when compared with other exogenous variables. The predictive relevance of the model was found substantial revealed Q2=40.5% relevance to predict employee retention. The moderating role of the competitive advantage was confirmed and directs that the positive relationship between employee retention and organizational performance will be stronger when competitive advantage is higher. Finally, results showed that intrinsic motivation had the highest importance level when compared with other constructs. Therefore, manager and policy makers should take into consideration intrinsic motivation and transformational leadership in order to boost employee retention and organizational performance.